Altered hippocampal expression of glutamate receptors and transporters in GRM2 and GRM3 knockout mice. - Lyon, L; Kew, J; Corti, C; Harrison, P; Burnet, P (2008)
Group II metabotropic glutamate receptors (mGluR2 and mGluR3, also called mGlu2 and mGlu3, encoded by GRM2 and GRM3, respectively) are therapeutic targets for several psychiatric disorders. GRM3 may also be a schizophrenia susceptibility gene. mGluR2-/- and mGluR3-/- mice provide the only unequivocal means to differentiate between these receptors, yet interpretation of in vivo findings may be complicated by secondary effects on expression of other genes. To address this issue, we examined the expression of NMDA receptor subunits (NR1, NR2A, NR2B) and glutamate transporters (EAAT1-3), as well as the remaining group II mGluR, in the hippocampus of mGluR2-/- and mGluR3-/- mice, compared with wild-type controls. mGluR2 mRNA was increased in mGluR3-/- mice, and vice versa. NR2A mRNA was increased in both knockout mice. EAAT1 (GLAST) mRNA and protein, and EAAT2 (GLT-1) protein, were reduced in mGluR3-/- mice, whereas EAAT3 (EAAC1) mRNA was decreased in mGluR2-/- mice. Transcripts for NR1 and NR2B were unchanged. The findings show a compensatory upregulation of the remaining group II metabotropic glutamate receptor in the knockout mice. Upregulation of NR2A expression suggests modified NMDA receptor signaling in mGluR2-/- and mGluR3-/- mice, and downregulation of glutamate transporter expression suggests a response to altered synaptic glutamate levels. The results show a mutual interplay between mGluR2 and mGluR3, and also provide a context in which to interpret behavioral and electrophysiological results in these mice.